Hollywood Hotel - Berkeley, Busby; Barnes, George; Rosher, Charles; Powell, Dick; Lane, Rosemary; Lane, Lola (The Busby Berkeley Collection, 2010)
This amusing little musical comedy was very loosely inspired by Hollywood Gossip Columnist, Louella Parsons' radio shadow, "Hollywood Hotel". Parsons appears as herself in the film and her show plays a minor part in the plot, but the real fun is in the comical hijinks, although much of it seems designed simply to showcase Benny Goodman and his orchestra. [www.threemoviebuffs.com]